Arktisk politik og regimedannelse i 2010’erne - Petersen, Nikolaj (Nordlit, 2012)
Recent developments have placed the High North on the international agenda. These include global warming, the prospects of major oil and gas finds, the opening of the Arctic Ocean to international shipping and the ongoing partition of its outer continental shelf between the five coastal states. In the so-called Ilulissat Declaration of 2008 these "Arctic Five" promised to play according to the UNCLOS rules and to shoulder their responsibility as coastal states. Despite this, the future may see both cooperation and conflict in the Arctic. The aim of the article is to discuss the possibilities of cooperative schemes, regimes, to regulate the problems which increasing shipping and extraction industries and fisheries may cause. First, a survey of future Arctic actors and fora is presented. While Arctic politics isstill dominated by the eight members of the Arctic Council, other actors, most clearly China, South Korea, Japan and the European Commission, are pressuring for influence. Furthermore, the Arctic Council is pressured by the "Arctic Five" and has reacted by establishing a secretariat and by adopting its first binding decision, anagreement on cooperation in search and rescue operations. Other relevant fora are the IMO, the WMO and UNCLOS. Next, an inventory of future "tasks" facing the Arctic nations is presented. They include defence tasks, sovereignty tasks, national authority tasks, and tasks, which can only (or best) be handled in regimes. Such regimes seem most needed with respect to international shipping. In the final section the discussion on possible regimes gets more concrete. Many tasks can best be handled by the IMO, but the Arctic Council, the WMO and UNCLOS have also roles to play. In particular, the five Arctic costal states have acrucial role as providers of specific regime services. Without their participation Arctic regime-formation is a non-starter,